2018
DOI: 10.1093/jisesa/iey023
|View full text |Cite
|
Sign up to set email alerts
|

Best Host Age of Anastrepha obliqua (Diptera: Tephritidae) for Multiplication of Four Native Parasitoids from the Americas

Abstract: The success of the mass rearing of parasitoids is directly related to host quality, and it requires selecting the best biological host age to ensure the optimal performance of the parasitoids released into the field. The larval development of the parasitoids Utetes anastrephae (Viereck) (Hymenoptera: Braconidae) and Odontosema anastrephae Borgmeier (Hymenoptera: Eucoilidae) and the pupal development of the parasitoids Coptera haywardi (Ogloblin) (Hymenoptera: Diapriidae) and Dirhinus sp. (Hymenoptera: Chalcidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Here we found that the sex ratio was female-biased, about 70% female (≈ 3:1) for both hosts used. This proportion coincides with that obtained by Poncio et al (2018), with a percentage of 65% using A. obliqua larvae as hosts. This proportion is adequate for the purposes of augmentative biological control.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here we found that the sex ratio was female-biased, about 70% female (≈ 3:1) for both hosts used. This proportion coincides with that obtained by Poncio et al (2018), with a percentage of 65% using A. obliqua larvae as hosts. This proportion is adequate for the purposes of augmentative biological control.…”
Section: Discussionsupporting
confidence: 90%
“…Although A. ludens is not considered a preferred host for U. anastrephae, it can be used as an alternative host because it is a species relatively easy to rear, being a high-quality host that is currently used to produce massively D. longicaudata (Orozco-Dávila et al 2017;Cancino et al 2020). Under laboratory conditions U. anastrephae successfully parasitizes 5-8 days old A. obliqua larvae (Poncio et al 2018) and 7-8 days old A. ludens larvae (Aluja et al 2009;Cancino et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such ecological regulation implies underlying intra‐ or interpopulation interactions (Berryman & Turchin, 2001) involving closely interacting species such as parasitoid guilds or generalist predators (Aluja et al, 2005; Dor et al, 2014; Montoya et al, 2016; Berrones‐Morales et al, 2020a). This assumption is supported by the significant impact of several species of native parasitoids on immature stages of A. obliqua under field conditions (Murillo et al, 2015; Poncio et al, 2018; Berrones‐Morales et al, 2020a) and the use of biological control for suppressing fruit fly populations under an AW‐IPM approach (Ovruski et al, 2000; Montoya et al, 2007). Therefore, we thought parasitoid guilds contribute to significant second and higher‐order feedback effects within the biological systems of these pest populations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mean longevity of D. alloeum, U. canaliculatus, and D. mellea provided water and food in the laboratory was only 12.9, 9.54, and 12.21 days, respectively (Forbes et al 2009;Hood et al 2015). In addition, Utetes anastrephae (Viereck) on average survived less than 10 days when provided honey (Stuhl et al 2011), and less than six days without food and water (Poncio et al 2018). If U. tabellariae does survive long periods in nature, then this in addition to the nondiapause trait (discussed above) could further allow individuals to exploit late-developing R. tabellaria or other fly species that develop as larvae in late summer.…”
Section: Discussionmentioning
confidence: 92%